A mitochondria-targetable colorimetric and far-red fluorescent probe for the sensitive detection of carbon monoxide in living cells. Issue 3 (30th November 2018) - Wang, Zuokai; Zhao, Ziyang; Wang, Ruikang; Yuan, Ruifang; Liu, Caiyun; Duan, Qingxia; Zhu, Weiwei; Li, Xiuyun; Zhu, Baocun
Abstract : A simple colorimetric and far-red fluorescent probe was developed for the first time to visualize the gasotransmitter carbon monoxide in subcellular mitochondria. Abstract : The development of techniques for monitoring the gasotransmitter carbon monoxide (CO) at the subcellular level is significant for elucidating its diverse cellular functions. Herein, a mitochondria-targetable, colorimetric and far-red fluorescent probeFR-CO is presented for tracking CO levels in the mitochondria of living cells. TheFR-CO probe can sensitively detect CO using a turn-on fluorescence spectroscopic method, with a detection limit of around 38.9 nM. Additionally, theFR-CO probe exhibits outstanding selectivity towards CO over other various bioactive molecules. Moreover, the obvious color change (from colorless to pink) of the probe makes it possible to visually detect CO in aqueous solution. Most importantly, the excellent response properties of theFR-CO probe enable its application in the tracking of fluctuations in the CO levels of mitochondria in living cells, and it is thus anticipated that this probe will be a novel tool for further investigating the biological functions of CO in subcellular mitochondria.